Prediction of Left Double-Lumen Tube Size by Measurement of Cricoid Cartilage Transverse Diameter by Ultrasound and CT Multi-Planar Reconstruction - Zhang, Chengchao; Qin, Xinlei; Zhou, Wenyi; He, Shuaijie; Liu, Ao; Zhang, Yu; Dai, Zhigang; Yin, Jiangwen (Frontiers in Medicine, 2021)
Background: Currently, there is no uniform standard for selecting the left double lumen tubes (LDLT). Advantages, such as safety and convenience of the ultrasonic technology, and measurement accuracy, make it more widely applied in the clinical anesthesia, and computed tomography (CT) multi-planar reconstruction (MPR) technology will certainly provide a more accurate measurement. For better application for thoracic surgery choice LDLT, relieving the injury to patients, and reducing the complications, this study will compare the two approaches. Methods: The first part, 120 cases of patients were selected according to the height and gender; recording the patient's optimum LDLT and measurement the transverse diameter of the cricoid cartilage (TD-C) by ultrasound and CT MPR, and then obtained the TD-C range measurement by ultrasound and CT MPR corresponding to different types of LDLT. The second part, total of 102 patients were divided into the ultrasound group and the CT MPR group. In the ultrasound group, TD-C was measured by ultrasound, the corresponding size for intubation was selected based on the conclusions derived from the first part. In the CT MPR group, TD-C was measured by CT MPR, the corresponding size of LDLT based on the conclusions derived from the first part. Results: In the first part, 120 patients were no significant difference in the basic characteristics (P > 0.05). The accuracy of selecting the LDLT by conventional experience, namely height and gender was 58.3%. Ultrasonic measurement TD-C range was as follows: 32 Fr <15.88, 35 Fr: 15.88–16.80, 37 Fr: 16.75–17.81, and 39 Fr > 17.80. CT MPR measurement TD-C range was as follows: 32 Fr <15.74, 35 Fr: 15.74–16.65, 37 Fr: 16.56–17.68, and 39 Fr > 17.65. In the second part, there was no significant difference in the basic characteristics between the two groups (P > 0.05). The accuracy of intubation in the ultrasound group was 90.2% and the corresponding in the CT MPR group was 94.1% (P > 0.05). Conclusions: The accuracy of selecting the LDLT based on TD-C is significantly higher than conventional experience; it can significantly reduce the post-operative complications and there was no statistical significance in the accuracy of LDLT selected for TD-C measurement by ultrasound vs. CT, and both of them could be safely used for the evaluation before intubation under anesthesia in thoracic surgery.